A Diastereoselective Route to Benzoannelated Bridged Sultams - Klochkova, Anastasiia A.; Rassadin, Valentin A.; Sokolov, Victor V. (Synthesis, 2021)
A practical diastereoselective method for the synthesis of benzoannelated tri- and tetracyclic bridged sultams has been developed. The synthetic route employs widely available, substituted o-iodoanilines and is based on intramolecular Michael addition followed by cycloalkylation with α,ω-dihaloalkanes, or vice versa. The target compounds were isolated in good yields and the diastereoselectivity of the reaction could be easily controlled by the order of Michael addition and cycloalkylation steps.
Keywords: heterocycles; bridged sultams; Michael addition; cycloalkylation; diastereoselective synthesis